Terra Incognita. Globalisering, ecologie en rechtvaardige duurzaamheid - Jacobs, Roger (Academia Press, 2006)
Despite all attempts by many governments in the world to ascribe to the Holy Grail of 'sustainable development', Ecosystem Earth is confronted with a gargantuan sustainability crisis. The West has seduced the rest of the world to copy its highly attractive, albeit unsustainable development paradigm. In a finite world the eco-impact of the global consumer class cannot be extrapolated to all human beings. The ecological crisis and the global justice issue are linked to each other as Siamese twins. Part 1 of Terra Incognita presents an environmental and economic analysis of the ecological crisis. Using the pre-analytical viewpoint of ecological economics, the authors develop a conceptual framework in which ecology and global justice are united in one vision. To unravel the roots of the contemporary crisis the authors describe in Part 2 the ecological history of the human-nature interaction. Based on an interdisciplinary approach they discuss the three historical lifestyles: those of the hunter-gatherers, the agrarian society and the industrial era. Finally, in Part 3 the authors explore potential systemic solutions, which need to keep or make the world livable. This innovative book is supported by the stimulating belief that the human future remains principally open and can still be influenced by each of us.